AB0818 Nitric oxide diffusion and pulmonary capillary blood volume measurement in scleroderma patients. (23rd January 2014) - Rizzo, M.; Zanatta, E.; Guarnieri, G.; Pigatto, E.; Favaro, M.; Cardarelli, S.; Riato, L.; Maestrelli, P.; Punzi, L.; Cozzi, F.
Abstract : Background: Carbon monoxide diffusing capacity test (DLCO) is a non invasive diagnostic method for interstitial lung disease (ILD) and pulmonary arterial hypertension (PAH), frequent and severe complications of systemic sclerosis (SSc). A DLCO reduction has been detected in early phases of both ILD and PAH. Objectives: The aim of this study was to evaluate if a diffusing capacity test using another gas, nitric oxide (DLNO), is able to distinguish the alveolar capillary membrane damage characteristic of ILD and the pulmonary microcirculation alterations typic of PAH in SSc patients. Other studies have evaluated DLNO in some pulmonary diseases, but not in SSc (1, 2). Evaluating DLNO is also possible calculate the lung capillary blood volume (LCV). Methods: The study was performed in 37 consecutive patients affected with SSc, 31 female and 6 male, mean age 53.86±13.61 yrs and with mean disease duration of 10±7 yrs. 18 patients were affected by diffuse and 19 by limited cutaneous form of SSc. ANA were positive in all patients, with anti-topoisomerasi I pattern in 17 cases, anti-centromere in 12, nucleolar in 5 and anti-RNA polymerase III in 3. SSc patients were divided into three groups: 12 with ILD (HRCT score >4), 8 with PAH (PAPs >40 mmHg), 17 without pulmonary complications (HRCT score <4 and PAPs <40 mmHg). Twenty healthy subjects, sex and age matched, were considered as controls. Patients were submitted to single breath CO and NO diffusion. DLCO, DLNO and ratio DLNO /DLCO were evaluated. LCV was also calculated, according to the Roughton-Foster equation (3, 4). Statistic analysis was performed by Mann-Whitney test. Results: DLCO and DLNO were significantly reduced in SSc patients in comparison to control subjects (p<0.01). DLCO and DLNO were significantly lower both in the group with ILD (p<0.05 and p<0.001 respectively) and in the group with PAH (p<0.005 and p<0.001 respectively), in comparison to patients without pulmonary complications. DLNO /DLCO was higher in the group with PAH (4.52), when compared to the group with ILD (4.29) and to the third group (4.40), but the differences were not significant. LCV values were significantly reduced in the group with ILD (p<0.005) and in that with PAH (p<0.001), but also in patients without pulmonary complications (p<0.01). Conclusions: These data suggest that DLNO is a further diffusion test able to detect complications as ILD or PAH in SSc patients. The ratio DLNO /DLCO is useful to identify SSc patients with different pulmonary impairment. Moreover the reduction of LCV values suggest that a lung microvascular damage is detectable even in SSc patients without evidence of pulmonary complications (ILD and PAH). References: Phansalkar A et al. Am J Respir Crit Care Med 2004;169:1034-1040. Dressel H et al. BMC Pulm Med 2009;16: 9-30. Roughton FLW et al. J Appl Physiol 1957; 11: 290-302. Guenard H et al. Respir Physiol 1987; 70:113-120. Disclosure of Interest: None Declared